Mental Health in the Workplace from the Perspective of Oncology Nurses in Iran: A Qualitative Descriptive Study - Mozhgan Soheili; Maryam Eghbali-Babadi; Fariba Jokar; Fariba Taleghani (Iranian Journal of Nursing and Midwifery Research)
Background: The workplace and the context in which oncology nurses work are unique due to the complex and dynamic nature of cancer care. Nurses who care for cancer patients are exposed to varying degrees of psychological pressure. The present study was conducted to explore oncology nurses’ perceptions regarding mental health in the workplace. Materials and Methods: This study was conducted in 2018–2019. The participants were recruited through purposive sampling from eight educational specialty cancer treatment centers in Iran. Data were collected through individual semistructured interviews and analyzed using the conventional qualitative content analysis method. The Consolidated criteria for Reporting Qualitative research (COREQ) checklist was used to document the report of the study. Results: The extracted concepts were classified into three main categories and 17 subcategories. The main categories included attention to nurses’ occupational stress-provoking factors, attention to emotional/psychological responses in the workplace, and healthy mental atmosphere in the workplace. Conclusions: The findings indicate that oncology nurses need to be supported to enhance their mental health in the workplace. The findings of this study could help policymakers and nurse managers to understand the importance of improving the mental health of nurses in cancer care. In this regard, it is essential to make the necessary plans and scientific decisions to design and provide strategies to alleviate workplace problems and improve nurses’ mental health.